IMPLEMENTASI ALGORITMA HORSPOOL PADA APLIKASI ISTILAH FASHION - Azhar Azhar; Nasib Marbun; Soeb Aripin; Efori Buulolo (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
The word fashion is synonymous with fashion, in today's digital era fashion has become a lifestyle that can introduce personality through fashion on social media. In the term fashion, there are many terms that form the basis of knowledge to match one's fashion. The term fashion is generally studied using foreign languages so that many ordinary people find it difficult to understand in more detail related to fashion terms so that there is a need for applications that adopt science related to the term fashion. An application that was built with the main objective to search for information such as fashion terms is inseparable from the existence of string matching. String matching can be interpreted as an activity that works to match something that is sought in a container with the contents stored in the container. Algortima string matching which is implemented to search for the meaning of the term fashion in this study is the Horspool algorithm. The horspool algorithm is a boyer-moore derivative algorithm, to go through the process when there is a mismatch of character patterns with text characters, the horspool algorithm uses bad-matches repeatedly until all the character patterns are found to have a match against the text. The results of the application built in this study can facilitate ordinary people who have difficulty finding information related to fashion terms more easily.Keywords: Implementation, Fashion Terms, Algorithms, Horspool